International Regimes in Sister City Partnerships: An Analysis of Sustainable Development Goals (SDGs) Adoption in Bandung-Kawasaki Collaboration - Ulung, Alessandro Kurniawan; Saputro, Pradono Budi; Setiawan, Yuli (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study examines the Sustainable Development Goals (SDGs) as an international regime, focusing on their role in shaping the Bandung–Kawasaki sister city partnership. The collaboration emphasizes joint efforts in waste management, water resource management, and air quality improvement. This research raises this question: “How do the SDGs influence the formation of the sister city partnership between the two cities?” Using a qualitative method and drawing on Martha Finnemore and Kathryn Sikkink’s Norm Life Cycle theory, the study finds that the rules, norms, and principles embedded in SDG Goals 11 and 12 prompted the city government to collaborate with Kawasaki in adopting this regime to address Bandung’s environmental challenges, particularly severe trash management issues. Through this partnership, Bandung seeks to leverage Kawasaki’s expertise and technology to advance its sustainable development agenda. Using the Bandung–Kawasaki partnership as a case study, this research contributes to shedding light on the role of SDGs as an international regime.‎